Kompetensi Profesional Pengaruh Motivasi Mengajar dan Fasilitas Sekolah Terhadap Kompetensi Profesional Guru Matematika SMA Se-Kota Pekanbaru - Fitri Ayu Ningtiyas; Riska Ayu Ardani; Dwi Iramadhani; Yulia Zahara; Nurul Afni Sinaga; Rifaatul Mahmuzah (FKIP Universitas Mataram, 2023)
This study aims to examine the influence of teaching motivation and school facilities on the professional competence of high school mathematics teachers because teaching motivation is something important to consider in reviewing the performance of a teacher, as well as facilities owned by schools, completeness of facilities at schools will optimize the learning process in class. In reviewing the effect of teaching motivation and school facilities on professional competence, an inferential analysis using multiple regression. This research type is a survey with a population all of high school mathematics teachers in Pekanbaru City. Questionnaires for teaching motivation and school facilities, as well as tests in the form of multiple choice and non-test in the form of questionnaires to measure professional competence were instruments in this study. The data for this study obtained from 33 high school mathematics teachers in Pekanbaru City, 33 fellow teachers, and 909 high school students in Pekanbaru City. The result show that teaching motivation affects the professional competence of teachers and school facilities do not affect professional competence.